De novo Transcriptome Assembly, Gene Annotation and SSR Marker Development in the Moon Seed Genus Menispermum (Menispermaceae) - Hina, Faiza; Yisilam, Gulbar; Wang, Shenyi; Li, Pan; Fu, Chengxin (Frontiers in Genetics, 2020)
The moonseed genus MenispermumL. (Menispermaceae) is disjunctly distributed in East Asia and eastern North America. Although Menispermum has important medicinal value, genetic and genomic information is scarce, without available molecular markers. In the current study, we used Illumina transcriptome sequencing and de novo assembly of the two Menispermum species to get the in-depth genetic knowledge. From de novo assembly, 53,712 and 78,921 unigenes were generated for M. canadense and M. dauricum, with 37,527(69.87%) and 55,211(69.96%) showing significant similarities against the six functional databases, respectively. Moreover, 521 polymorphic EST-SSRs were identified. Of them, 23 polymorphic EST-SSR markers were selected to investigate the population genetic diversity within the genus. The newly developed EST-SSR markers also revealed high transferability among the three examined Menispermaceae species. Overall, we provide the very first transcriptomic analyses of this important medicinal genus. In addition, the novel microsatellite markers developed here will aid future studies on population genetics and phylogeographic patterns of Menispermum at the intercontinental geographical scale.